Prognostic Significance of Markers of Endothelial Dysfunction in Case of Severe Combined Blunt Abdominal Trauma - V. V. Aleksandrov; S. S. Maskin; N. K. Ermolayeva; V. N. Perfilova; V. V. Matyukhin; M. N. Alimov; D. S. Biriulev; A. Rachid; S. M. Sigaev (Неотложная медицинская помощь)
INTRODUCTION. In case of polytrauma, an imbalance occurs between substances produced by the endothelium, the rheological properties of the blood are disrupted, the content of procoagulants increases, the permeability of the vascular wall increases, which contributes to thrombus formation and increased tissue hypoxia, and subsequently to the development of multiple organ failure, and, of course, affects the course of traumatic disease, the development of complications and mortality. However, specific markers of endothelial dysfunction and their levels, by which it is possible to reliably predict the course of traumatic disease in severe combined closed abdominal trauma for the appropriate pathogenetic treatment have not yet been determined.AIM OF THE STUDY. To determine the significance of some markers of endothelial dysfunction (C-reactive protein, von Willebrand factor, the number of desquamated endothelial cells in the blood) in combined blunt abdominal trauma to predict the likelihood of complications and adverse outcomes.MATERIAL AND METHODS. The main group consisted of 31 patients with severe combined blunt abdominal trauma, the comparison group consisted of 5 patients operated on for large ventral hernias. All patients underwent blood tests for C-reactive protein, von Willebrand factor, the number of desquamated endothelial cells.RESULTS. The level of all three considered markers of endothelial dysfunction in severe abdominal trauma significantly differs from that in operated non-traumatized patients, which allows differential diagnostics to be made between abdominal wall contusion and damage to internal organs; extremely high values suggest an unfavorable course of traumatic disease and a high probability of a fatal outcome.CONCLUSION. Taking into account that the development of traumatic disease is based on damage to the vascular endothelium, it is necessary to consider as prognostic indicators changes in the level of activity of C-reactive protein, von Willebrand factor, desquamated endothelial cells in patients with severe combined blunt abdominal trauma.